22nd International Conference and Exhibition on Electricity Distribution (CIRED 2013) 2013
DOI: 10.1049/cp.2013.0712
|View full text |Cite
|
Sign up to set email alerts
|

Seismic vulnerability assessment of electric power distribution network in Iran

Abstract: In this paper, the most important activities for increase the seismic reliability and safety level of Electric Power Distribution Network (EPDN) in IRAN are presented. TAVANIR Co. as the manager of production, transmission and distribution of electricity in IRAN with the cooperation of NRI carried out a research project to develop seismic assessment and rehabilitation guideline of EPDN of IRAN and Crisis Management implementation. As the consequences, two guidelines have been developed and Great Tehran Electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…[29]) have also been accounted for. A large number of specific studies on earthquake experiences and on the vulnerability of elements of the infrastructure have also been considered; see the references from [30][31][32][33][34][35][36][37].…”
Section: Methodology Of Assessmentsmentioning
confidence: 99%
“…[29]) have also been accounted for. A large number of specific studies on earthquake experiences and on the vulnerability of elements of the infrastructure have also been considered; see the references from [30][31][32][33][34][35][36][37].…”
Section: Methodology Of Assessmentsmentioning
confidence: 99%
“…3. Importance factor (I) based on "Seismic Vulnerability evaluation of Electric Power Distribution Networks" [8]. 4.…”
Section: Capacity Curve Instructionsmentioning
confidence: 99%
“…There are some research activity has been reported about seismic behaviour of EPDN components. [1], [2], [3]. Toward such objective, TAVANIR Co. as the manager of production, transmission and distribution of electricity in IRAN with the cooperation of NRI proceeded to develop seismic assessment and rehabilitation guideline of power distribution network of IRAN and Crisis Management implementation.…”
Section: Introductionmentioning
confidence: 99%